Reptant Eagle : Essays on Carlos Fuentes and the Art of the Novel. - Cantú, Roberto (Cambridge Scholars Publishing, 2015)
Carlos Fuentes (1928-2012) was the most prominent novelist in contemporary Mexico and, until his recent death, one of the leading voices in Latin America's Boom generation. He received the most prestigious awards and prizes in the world, including the Latin Civilization Award (presented by the Presidents of Brazil, Mexico, and France), the Miguel de Cervantes Prize, and the Prince of Asturias Award. During his fecund and accomplished life as a writer, literary theorist, and political analyst, Fuentes turned his attention to the major conflicts of the twentieth century - from the Second World W.